Exercício físico na prevenção de quedas em idosos institucionalizados - Tomicki, Camila (2015)
This study aimed to determine whether physical exercise helps in the prevention of falls in institutionalized elderly. This is a randomized controlled clinical trial, conducted in two Long-stay Philanthropic Institutions for the Elderly located in a city in the northern region of Rio Grande do Sul, Brazil. Participants were divided into control (G1) and intervention groups (G2). G1 was told not to perform any type of intervention, whereas G2 was told to participate in an exercise program three times a week for twelve weeks. The groups were evaluated by the Berg Balance Scale (BBS), the Timed Up and Go Test (TUGT), the Manual Muscle Test (MMT) and the Chair Lift Test (CLT). The results were compiled in two scientific productions, which are attached to this study. The first production is entitled "Balance and Falls Risk in Institutionalized Elderly undergoing a Physical Exercise Program: Randomized Clinical Trial", and aimed to determine the association between postural balance and the risk of falls in institutionalized elderly who joined an exercise program. After the intervention, G2 showed better scores in both the BBS and the TUGT, which indicates a significant improvement in body balance and a decrease in the risk of falls when compared to G1. We also verified a statistically significant association between the BBS and the TUGT. Based on the first scientific production, we could find an association between postural balance and risk of falls in institutionalized elderly before and after an exercise program. The second production, entitled "Relationship between Falls and Muscle Strength in Institutionalized Elderly who are physical exercise practitioners or non", aimed to verify the relationship between the risk of falls and their muscle strength. After the first study, we could observe a statistically significant association between the risk of falls score and muscle strength. After scientific production II, we could see that there was an association between the pre and post intervention regarding muscle strength with the risk of falls, which showed us the importance of exercises to gain and/or maintain muscle strength of institutionalized elderly. After the end of the study, we could conclude that the regular practice of physical exercise has to be an important strategy for the prevention of falls in institutionalized elderly